Chemical characterization and encapsulation of Ganoderma pfeifferi extract with cytotoxic properties - Šťastný, Jan; Morellá-Aucejo, Ángela; Skala, Tomáš; Bernardos, Andrea; Maršík, Petr; Lérida-Viso, Araceli; Matějka, Jaroslav; Mascellani Bergo, Anna; Marcos, María Dolores; Martínez-Máñez, Ramón; Jablonský, Ivan; Klouček, Pavel (Frontiers in Pharmacology, 2025)
Mushrooms of the genus Ganoderma are known for diverse biological activities, demonstrated both traditionally and experimentally. Their secondary metabolites have shown cytotoxic potential across different cancer cell lines. Besides exploration of the most active components in different species or genotypes, new formulation techniques are in development. In recent years, there has been a growing interest in the use of nanomaterials because of significant potential for pharmacology applications as substance carriers. Applying nanoparticles may enhance the medicinal effect of the mushroom substances. This study investigated the cytotoxic properties of Ganoderma species methanolic extracts against the HeLa cancer cell line. Notably, the extract obtained from Ganoderma pfeifferi demonstrated the highest activity and was further used for encapsulation within synthesized mesoporous silica nanoparticles MCM-41. Subsequently, the cytotoxic effect of the loaded MCM-41 to the free form of extract was compared. The obtained results indicate successful encapsulation, and similar activity comparing encapsulated form to free extracts (IC50 16.6 μg/mL and 20.5 μg/mL, respectively). In addition, the four unique compounds were identified as applanoxidic acid A, applanoxidic acid G, ganoderone A, and ganoderone B in the G. pfeifferi. This study is an essential prerequisite for further steps like nanoparticle functionalization for sustained or on-command delivery of these natural extracts.